2020
DOI: 10.46928/iticusbe.756426
|View full text |Cite
|
Sign up to set email alerts
|

Covi̇d-19 Süreci̇nde İli̇şki̇leri̇nde Sorun Yaşayan Çi̇ftlere Yöneli̇k Duygu Odakli Ai̇le Danişmanliği

Abstract: 2019 yılının sonlarında ortaya çıkarak dünyaya yayılan corona virüs sonucu yaşanan kısıtlama ve karantina süreçleri çift ilişkilerini ve aile dinamiklerini olumsuz yönde etkilemiştir. Çift ilişkileri açısından bu dönem değişime adaptasyon, belirsizlikleri tolere edebilme ve kısıtlamalara uyum sağlama yanında özellikle de duygu düzenleme, stres ve kaygı yönetimi gibi becerilerin etkili bir şekilde kullanımını gerektiren kritik bir dönem olmuştur. Olası krizlere karşı duyguları fark etme, tanımlama, normalleştir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…In Bozkurt’s (2020) study on the impact of Covid-19 on family relationships involving 5338 people, 40% of the participants stated that they had concerns about meeting their basic needs. Yıldız and Erdem (2020) pointed out that job insecurity was an important indicator in terms of family ties and that the fear of going hungry affected family communication and caused problems. Kaya & Akın, 2021 examined the negative impacts of the pandemic on family and marital life and concluded that children experienced both mental and behavioral problems causing them to perform worse at school.…”
Section: Discussionmentioning
confidence: 99%
“…In Bozkurt’s (2020) study on the impact of Covid-19 on family relationships involving 5338 people, 40% of the participants stated that they had concerns about meeting their basic needs. Yıldız and Erdem (2020) pointed out that job insecurity was an important indicator in terms of family ties and that the fear of going hungry affected family communication and caused problems. Kaya & Akın, 2021 examined the negative impacts of the pandemic on family and marital life and concluded that children experienced both mental and behavioral problems causing them to perform worse at school.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in line with the developed model and considering the systematics of the model. There are very few case studies in the field of family counseling in Turkey (Civan Gökkaya & Nazlı, 2019;Demirbilek, 2016;Fışıloğlu, 1992;GülçinYıldız, 2020;Türkmen & Erkükçü Akbaş, 2021;Üstündağ, 2014). However, no case studies were conducted on how the spirituality dimension can be used in family counseling.…”
Section: Spiritually-directed Family Therapymentioning
confidence: 99%
“…Bu süreçte büyük bir özveri ve tehdit altında çalışan sağlık çalışanlarının da aile üyelerine de hastalık bulaştırma korkusu yaşadıkları ortaya çıkarılmıştır (Arzık, 2022). Kılınç (2021) (Yıldız, 2020). Aile bireylerinin bir arada evde fazla zaman geçirmeleri çeşitli sorunların yaşanmasına neden olmuştur (Çetin ve Aral, 2022).…”
Section: İstatistik Analizunclassified